2015
DOI: 10.1259/bjr.20140548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neovascularization with spectral computed tomography in a rabbit VX2 liver model: a comparison with real-time contrast-enhanced ultrasound and molecular biological findings

Abstract: Objective: To validate the feasibility of using the parameters of spectral CT and CT perfusion and the dynamic features of real-time contrast-enhanced ultrasound (CEUS) to evaluate the vascularization of VX2 hepatic tumours. Methods: Spectral CT imaging, CT perfusion and CEUS analysis were performed on rabbits implanted with VX2 hepatic tumours, 7 and 14 days after implantation. The perfusion parameters of CT, normalized iodine concentration (NIC) and dynamic features of CEUS were measured in the rim of the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…To acquire more concrete proof that TAEMA is an effective and feasible strategy, the real-time relative-quantitative polymerase chain reaction (Q-PCR) was used to investigate the expressive changes of important genes related to the HCC, including tumor protein p53 (p53), 51 aldehyde dehydrogenase 1 family (ALDH1A1, also known as retinaldehyde dehydrogenase 1), 52 and vascular endothelial growth factor (VEGF), respectively. 53 In fact, p53 possesses sophisticated mechanisms of anticancer function and plays a role in apoptosis, genomic stability, and inhibition of angiogenesis. Meanwhile, the enzymatic activity of ALDH1A1 has been identified as one of the markers of cancer stem cells, and the high expression is associated with prognosis in a variety of solid tumors.…”
Section: Resultsmentioning
confidence: 99%
“…To acquire more concrete proof that TAEMA is an effective and feasible strategy, the real-time relative-quantitative polymerase chain reaction (Q-PCR) was used to investigate the expressive changes of important genes related to the HCC, including tumor protein p53 (p53), 51 aldehyde dehydrogenase 1 family (ALDH1A1, also known as retinaldehyde dehydrogenase 1), 52 and vascular endothelial growth factor (VEGF), respectively. 53 In fact, p53 possesses sophisticated mechanisms of anticancer function and plays a role in apoptosis, genomic stability, and inhibition of angiogenesis. Meanwhile, the enzymatic activity of ALDH1A1 has been identified as one of the markers of cancer stem cells, and the high expression is associated with prognosis in a variety of solid tumors.…”
Section: Resultsmentioning
confidence: 99%
“…VEGF, one of the most prominent biomarkers of angiogenesis studied to date, has been shown to correlate well with CT perfusion in peripheral pulmonary nodules[ 28 ]. Moreover, the study of Zhou et al[ 13 ] in a rabbit VX2 liver model suggested that nIC and contrast-enhanced ultrasound parameters positively correlated with VEGF and FGF2 expression, while several reports failed to show such a correlation, for example, the GC study performed by Yao et al[ 6 ] and the colorectal cancer research by Goh et al[ 24 ]. The relationship between VEGF expression and imaging of tumor vascularity is complex.…”
Section: Discussionmentioning
confidence: 99%